2019
DOI: 10.1017/s0033291719001004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, comorbidities, and correlates of atypical depression: evidence from the UK Biobank Mental Health Survey

Abstract: BackgroundDepression is a heterogeneous disorder with multiple aetiological pathways and multiple therapeutic targets. This study aims to determine whether atypical depression (AD) characterized by reversed neurovegetative symptoms is associated with a more pernicious course and a different sociodemographic, lifestyle, and comorbidity profile than nonatypical depression (nonAD).MethodsAmong 157 366 adults who completed the UK Biobank Mental Health Questionnaire (MHQ), N = 37 434 (24%) met the DSM-5 criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 46 publications
(94 reference statements)
9
82
0
Order By: Relevance
“…The lifetime prevalence of depression in females is twice as that in males (9,10). Females with MDD tend to show younger age of onset (11), longer duration (12), more severe and recurrent episodes (13), higher comorbidity of anxiety, lower comorbidity of substance use, greater functional impairment (11), and lower quality of life (14) than male patients. In the clinical symptomatology, females with MDD report higher rates of increased appetite and weight gain, somatic concern, and hypochondriasis than their male counterparts (12,15).…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime prevalence of depression in females is twice as that in males (9,10). Females with MDD tend to show younger age of onset (11), longer duration (12), more severe and recurrent episodes (13), higher comorbidity of anxiety, lower comorbidity of substance use, greater functional impairment (11), and lower quality of life (14) than male patients. In the clinical symptomatology, females with MDD report higher rates of increased appetite and weight gain, somatic concern, and hypochondriasis than their male counterparts (12,15).…”
Section: Introductionmentioning
confidence: 99%
“…The aims of the current study were to identify datadriven subtypes of depressive symptoms in young people (aged [15][16][17][18][19][20][21][22][23][24][25] with MDD and to compare potential . A severe depression with increased appetite (SIA) subtype, severe depression with decreased appetite and insomnia (SDA) subtype and a moderate depression (MOD) subtype were identified in both datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of leptin, inflammatory markers (C-reactive protein (CRP), interleukin-6 (IL-6), interleukin 1 receptor antagonist (IL-1RA) and tumor necrosis factor-α (TNF-α)), insulin and higher BMI are associated with the atypical or increased appetite subtype 15,[19][20][21] . Conversely, higher cortisol and ghrelin levels are associated with the more typical subtype characterized by decreased appetite 19,[21][22][23] . In addition, genetic studies have shown that the atypical subtype with increased appetite is associated with a higher polygenic risk score for BMI, leptin and CRP, whereas the typical subtype showed a stronger association with polygenic risk scores for psychiatric disorders such as schizophrenia 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The aims of the current study were to identify data-driven subtypes of depressive symptoms in young people (aged [15][16][17][18][19][20][21][22][23][24][25] with MDD and to compare potential structural brain alterations between these subtypes. The data-driven symptom subtypes found in the YoDA study cohort were in line with the subtypes characterized by opposite neurovegetative symptoms previously identified in adults (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%